Platelet Responses in Cardiovascular Disease: Sex-Related Differences in Nutritional and Pharmacological Interventions - Valeria Gasperi; M. Valeria Catani; Isabella Savini (Hindawi-Wiley, 2020)
Cardiovascular diseases (CVD) represent one of the biggest causes of death globally, and their prevalence, aetiology, and outcome are related to genetic, metabolic, and environmental factors, among which sex- and age-dependent differences may play a key role. Among CVD risk factors, platelet hyperactivity deserves particular mention, as it is involved in the pathophysiology of main cardiovascular events (including stroke, myocardial infarction, and peripheral vascular injury) and is closely related to sex/age differences. Several determinants (e.g., hormonal status and traditional cardiovascular risk factors), together with platelet-related factors (e.g., plasma membrane composition, receptor signaling, and platelet-derived microparticles) can elucidate sex-related disparity in platelet functionality and CVD onset and outcome, especially in relation to efficacy of current primary and secondary interventional strategies. Here, we examined the state of the art concerning sex differences in platelet biology and their relationship with specific cardiovascular events and responses to common antiplatelet therapies. Moreover, as healthy nutrition is widely recognized to play a key role in CVD, we also focused our attention on specific dietary components (especially polyunsaturated fatty acids and flavonoids) and patterns (such as Mediterranean diet), which also emerged to impact platelet functions in a sex-dependent manner. These results highlight that full understanding of gender-related differences will be useful for designing personalized strategies, in order to prevent and/or treat platelet-mediated vascular damage.